POPULASI ELAEDOBIUS KAMERUNICUS PADA TANAMAN KELAPA SAWIT YANG BERBEDA UMUR DI KECAMATAN RASAU JAYA, KABUPATEN KUBU RAYA - Muhammad Amin Prabowo; Tris Haris Ramadhan; Edi Syahputra (Fakultas Pertanian Universitas Tanjungpura, 2021)
Pollination in oil palm is generally carried out by insects. The beetle Elaeidobius kamerunicus is one of the effective pollinating insects for oil palm. This beetle breeds well on male flowers, this beetle can also reach female flowers located in the inner bunch, so this condition causes more perfect pollination. This study aims to determine the population of oil palm pollinating insects E. kamerunicus at several ages of oil palm plants which will be associated with environmental factors and ways of oil palm cultivation, both application of pesticides and fertilizers in Rasau Jaya District, Kubu Raya Regency. Insect sampling in this study used a purposive sampling method (determined sample), which used 3 plant blocks with different age groups of 4, 6, and 9 years respectively. The method used is the observation method, namely observing the population of oil palm pollinating insects directly on oil palm flowers. Observations were made on the population of E. kamerunicus by counting the number of E. kamerunicus visiting blooming oil palm flowers obtained from yellow sticky traps with a size of 20x30 cm placed near oil palm flowers. The results of the study concluded that the older the age of the oil palm plant, the greater the number of spikelets and the population of E. kamerunicus insects increased.